THE ROLE OF LEARNING STYLE TOWARDS STUDENT’S ACHIEVEMENT: A CASE STUDY OF A STUDENT OF SENIOR HIGH SCHOOL - Irham Miftakhul Jannah; Mira Patlasari; Rif’atus Syaniyah (Jurnal Bahastra, 2018)
Language is kind of the difficult set of skills that students are able to learn. There is no easy way to master a language, particularly a language which is not our first language. In the process of learning a language particularly a second language, there are many factors that determine the success of learning; one of the factors is learning styles. This paper focuses to study an eleventh grader student in vocational high school. The main point of the research was to determine the learning style of student when she is learning and gaining knowledge, especially in learning English. This research also contributes to reveal the role of learning style that played in the learning process and find the factors that make student achieve better in learning English. Instruments used to collect data were interviews, field notes, and student’s report. To analyze the data gathered from the data collection, I used triangulation. The findings shown that student will achieve better when she feel comfortable to study, without compulsion and intervention outside the context of the material. At the side of other aspect, to learn English, student’s ability is not only gained from teachers’ explanation in classroom, but also from other media. By considering these findings, I suggest that teachers have to aware about the learning style of their students, and for the students who have difficulties in learning English, try to find different ways in learning to gain the knowledge and ability in English language.